Probability Theory - Loeve, Michel (New York: Van Nostrand Reinhold, 1963)
The foundations of this publication are presented in: the Introductory Part on the background of the concepts and problems, treated without advanced mathematical tools; Part One on the notions of measure theory that every probabilist and statistician requires; Part Two on general concepts and tools of probability theory; Part Three on independence devoted essentially to sums of independent random variables and their limit properties; Part Four on dependence devoted to the operation of conditioning and limit properties of sums of dependent random variables; and Part Five on elements of random analysis devoted to the basic concepts of random analysis and to the martingale, decomposable, and Markov types of random functions.
Includes bibliographical references and indexes.
ne 23/03/2018
Loan
Keywords: Probability Theory